Evaluasi Pelaksanaan Program Kota Tanpa Kumuh - Dela Ananda; Reiki Nauli Harahap; Arkanudin Arkanudin; Riska Nawila; S Visi Ananda; Stephanie Gloria Paska Bertho (Universitas Musamus, Merauke, Papua, 2024)
Management of slum areas, especially in urban areas, is a very important element in management, development and public service efforts. The dominant factors that occur in slum areas include: uncontrolled population growth and lack of effective urban planning. The aim of this research is to evaluate the implementation of the KOTAKU program in Pontianak City. This research method uses a descriptive - qualitative approach with data collection techniques in the form of purposive sampling through observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, and data verification. The results of this research show that the evaluation of the implementation of the KOTAKU program in Pontianak City in terms of the 7 indicators that have been analyzed is included in the moderate slum category, and has been good in terms of community participation and relationships between related parties involved in implementing the development of the KOTAKU program. The programs that have been running in Pontianak City are in line with the main objective of the KOTAKU program to increase slum residents' access to basic infrastructure and better public services, especially the improvement and development of various aspects such as buildings, road environments, drinking water supply, environmental drainage, management. wastewater, waste disposal, public open space and fire safety. The KOTAKU program has been implemented well by facilitators who coordinate with sub-district officials, so that hearings with the community regarding maintenance of the KOTAKU area can run well..